The Power of Positive Participation: Meaningfully Engaging Young People in Health Research - Robertson, Sarah; Campbell, Archie; Flaig, Robin; Whalley, Heather; Milbourne, Hannah; Kirby, Liz; Tatham, Rosie; Buchanan, David; Clark, Fiona; Richmond, Anne; Xiao, Zhuoni; Sudlow, Cathie (International Journal of Population Data Science, 2025)
Objectives We actively involve young people in shaping health research by gathering feedback from diverse groups. Our goal is to improve youth engagement and inform research practices. These groups have influenced decisions in our longitudinal health study, aligning with children's rights and challenging tokenistic assumptions for meaningful engagement. Methods We have developed positive healthy relationships with young people and stakeholders through the development of Youth Advisory Groups, consisting of a diverse group of young people from across the country and the establishment of a new Mental Health Youth Forum, the creation of new social media accounts and development of “young people friendly” materials. We have also given young people a voice in ethics submissions, and a platform to share their journey at national conferences, enhanced partnerships with youth work organisations and developed a lesson plan for secondary schools to raise awareness of health research. Results After feedback from young people we have significantly redesigned our youth communication and recruitment pathways, including text-based communication and compensating time. 12-15 year-olds can now initiate the process of joining the study without a parent/guardian joining first, consistent with children’s rights-based approaches. Youth co-production has also been central to projects, ensuring age appropriate resources, engagement with new technology, raising awareness of health research and optimising and maintaining engagement. Within 1 month of launch, 37 schools have engaged with the new lesson plans from 65% of local authority areas. Young people have made a meaningful contribution to our research projects, and contributed social media content to disseminate knowledge and highlight the importance of young people’s engagement in health research. Conclusions Insight from young people has strengthened research design and increased participant engagement. Information about how to contact young people has led to system changes to remove barriers and allow young people to be heard. Effective communication strategies with young people will benefit future research involving the younger generation.